Job Satisfaction and Organizational Commitment of Professional Married Women - Manandhar, Sushma (PYC Nepal Journal of Management, 2021)
An empirical study aimed at identifying and quantifying the association between job satisfaction and organizational commitment of officer and non-officer level professional married women working in commercial banks within Kathmandu valley. A total of 120 professional married women, 73 officer level and 47 non-officer level professional married women from banks were included. The study followed descriptive and analytical research design. The reliability analysis, Pearson correlation and regression analyses were carried on to test the proposed hypotheses. The Cronbach’s alpha also showed reliability of the given variables under the study. Results showed more significant associations between job satisfaction and organizational commitment exist in non-official level than overall levels (officer and non officer level) and officer level professional married women respectively. Thus, job satisfaction influenced significantly to organizational commitment in non-officer level, overall levels and officer levels professional married women. Thus, more attention should be given to the professional married women in the officer level job position for improvement job satisfaction and commitment from individual and organizational level.